Nurse-Led Phone Call Follow-Up Clinics Are Effective for Patients With Prostate Cancer. (September 2017) - Casey, RG; Powell, L; Braithwaite, M; Booth, CM; Sizer, B; Corr, JG
Introduction: The rising cost of healthcare requires rethinking in terms of resource utilisation care delivery. Nurse-led PSA phone follow-up clinics may provide a suitable option. Materials and methods: 815 patients were recruited for the nurse-led stable prostate cancer telephone follow-up service. A convenience sample was selected for postal questionnaire assessment of their satisfaction. Results: 815 patients had 3683 phone-call follow ups over 10 years. Patients' own understanding of condition varied from average (76.3%) and good (9.2%) in the majority. 87.2% found the service convenient and 75.6% informative. 95.3% found the telephone assessment preferable to attending the outpatient department. 87.2% were keen on savings on transport/travel. 53.5% found it more reassuring. 91.9% of patients felt that everything they wanted to talk about was covered. Discussion: This service can be delivered in a high volume nurse-led service, with high levels of patient satisfaction, as an innovative service development.